Global effects of extreme temperatures on wild bumblebees. Issue 5 (16th March 2021) - Martinet, Baptiste; Dellicour, Simon; Ghisbain, Guillaume; Przybyla, Kimberly; Zambra, Ella; Lecocq, Thomas; Boustani, Mira; Baghirov, Ruslan; Michez, Denis; Rasmont, Pierre
Abstract: Climate plays a key role in shaping population trends and determining the geographic distribution of species because of limits in species' thermal tolerance. An evaluation of species tolerance to temperature change can therefore help predict their potential spatial shifts and population trends triggered by ongoing global warming. We assessed inter‐ and intraspecific variations in heat resistance in relation to body mass, local mean temperatures, and evolutionary relationships in 39 bumblebee species, a major group of pollinators in temperate and cold ecosystems, across 3 continents, 6 biomes, and 20 regions (2386 male specimens). Based on experimental bioassays, we measured the time before heat stupor of bumblebee males at a heatwave temperature of 40 °C. Interspecific variability was significant, in contrast to interpopulational variability, which was consistent with heat resistance being a species‐specific trait. Moreover, cold‐adapted species are much more sensitive to heat stress than temperate and Mediterranean species. Relative to their sensitivity to extreme temperatures, our results help explain recent population declines and range shifts in bumblebees following climate change. Abstract : Article impact statement : There is interspecific variation in heat stress of bumblebee males exposed to extreme high temperatures. Abstract : Efectos Globales de las Temperaturas Extremas sobre Abejorros Silvestres Resumen: El clima juega un papel importante en la configuración de las tendencias poblacionales y en la determinación de la distribución geográfica de las especies debido a los límites de la tolerancia térmica y al agua que tiene cada especie. Por lo tanto, una evaluación de la tolerancia de las especies al cambio térmico puede ayudar a predecir los potenciales cambios espaciales y las tendencias poblacionales detonadas por el calentamiento global en curso. Evaluamos las variaciones inter‐ e intraespecíficas de la resistencia al calor en relación con la masa corporal, temperaturas locales promedio y las relaciones evolutivas para 39 especies de abejorros, un grupo primordial de polinizadores en ecosistemas templados y fríos, en tres continentes, seis biomas y 20 regiones (2, 386 especímenes machos). Con base en bioanálisis experimentales, medimos el tiempo previo al letargo por calor de los abejorros machos a temperaturas de 40 °C, típicas de una ola de calor. La variabilidad interespecífica fue significativa, en contraste con la variabilidad interpoblacional, lo cual fue consistente con el hecho de que la resistencia al calor sea una característica específica de la especie. Además, las especies adaptadas al frío son mucho más sensibles al estrés por calor que las especies de clima templado o Mediterráneo. En relación con la sensibilidad a las temperaturas extremas, nuestros resultados ayudan a explicar las recientes declinaciones poblacionales y cambios en la distribución de los abejorros posteriores al cambio climático.